Evaluation of resistance and susceptibility level of single and double gene Bt cotton against Armyworm and American bollworm - Muhammad Amjad; Hafiza Masooma Naseer Cheema; Jam Nazeer Ahmad; Kashif Noor; Haram Aziz Alvi; Hanan Ahmad; Zobia Anwer (International Journal of Applied and Experimental Biology)
Bt cotton was developed against lepidopteran insects and got a significant attraction by the Pakistani farmers to control target pests. The experiment was conducted to determine the resistance and susceptibility level of lepidopteran insects against double gene (Cry1Ac + Cry2A) and single genes Cry1Ac and Cry2A. Six Bt cotton genotypes G1 and G2 with Cry1Ac, G5 and G6 with Cry2A, and G3 and G4 with double gene (Cry1Ac + Cry2A) were studied. G7 was non-Bt which was used as a control. A qualitative test of Bt genes was done with immune-blot strips, and quantification was done by the ELISA technique. In the Armyworm bioassay, G1 and G2 showed 1.187 mg g-1 and 0.927 mg g-1 concentrations of Cry1Ac and 41.66% and 33.33% larval mortality, respectively. The Cry2A genotypes, G5 and G6, showed 7.60 mg g-1 and 7.79 mg g-1 concentrations of Cry2A, respectively, and larval mortality as 83.33% on both genotypes. The double gene genotypes, G3 and G4, showed Cry1Ac concentrations as 0.803 mg g-1 and 0.730 mg g-1, those of Cry2A 7.459 mg g-1 and 7.407 mg g-1, whereas the larval mortality of the two genotypes had been 91.67% and 100%, respectively. In the American bollworm bioassay, G1 and G2 showed concentration of Cry1Ac as 1.049 mg g-1 and 1.052 mg g-1 and larval mortality 33.33% and 41.66%, respectively. G5 and G6 showed Cry2A concentrations as 6.520 mg g-1 and 6.464 mg g-1 and the larval mortality levels as 66.67% and 58.33%, respectively. G3 and G4 showed concentrations of Cry1Ac and Cry2A as 1.460 mg g-1 and 0.968 mg g-1, and 6.025 mg g-1 and 6.651 mg g-1 and the larval mortality as 100% and 91.66%, respectively. Low weight gain was observed on those genotypes which contained double gene rather than any of the single genes. Strong positive correlations existed between insect’s mortality and double gene concentration. A lethal concentration (LC) of the double gene of Armyworm and American bollworm was 7.513 mg g-1 and 7.684 mg g-1, respectively, required to kill 99% of the insect’s population. Double gene Bt cotton genotypes had resistance against target pests, while single-gene Bt cotton genotypes lost their efficacy against the target pests.